Character Growth Following Collective Life Events: A Study on Perceived and Measured Changes in Character Strengths During the First Wave of the COVID-19 Pandemic. Issue 4 (July 2022) - Gander, Fabian; Wagner, Lisa
Did the COVID-19 pandemic promote character growth? Studies using sequential samples suggest that collective life events can result in character growth, but their conclusions have been questioned. This study used three approaches to examine character growth during the first wave of the pandemic: perceived changes in oneself and in a close other, and a longitudinal analysis of changes. In addition, we tested whether character strengths assessed before the pandemic predicted specific instances of growth, that is, engagement in volunteering and compliance with regulations during the pandemic. German-speaking participants ( N  = 366, 76.5% female, mean age: 45.33 years) who had completed an assessment of character strengths before the pandemic reported on perceived changes in character strengths, engagement in volunteering, and compliance with regulations. A subsample also completed a second assessment of character strengths. The results showed that (a) participants reported perceived changes for most character strengths in both themselves and close others, while (b) longitudinal increases were only observed for humility and prudence. Pre-pandemic character strengths predicted (c) engagement in volunteering and (d) compliance with regulations. We conclude that actual character growth was smaller than the perceived changes but that the character strengths did predict relevant behaviors related to the COVID-19 pandemic.